Highly adhesive negative photosensitive polyimide resin glue solution, its preparation method and use
Patent Information
- Application Number
- CN202611001451.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-07
- Publication Date
- 2026-10-23
AI Technical Summary
[0037]通过在聚酰胺酸酯主链中引入含硅氧烷结构二酐,协同光交联剂、热交联剂、低温固化促进剂、助粘剂及增韧剂等组分,使固化树脂薄膜兼具高铜面粘结性、优良光刻工艺性(分辨率≤8.0 μm,陡直度≥0.5)、高力学性能(拉伸强度≥100 MPa,断裂伸长率≥40%)、耐湿热性、耐化学浸蚀性,且残余内应力≤30 MPa,显著降低重构晶圆翘曲变形,避免RDL层间开裂。
Smart Images

Figure SMS_3 
Figure QLYQS_1 
Figure QLYQS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer materials technology, specifically to a highly adhesive negative photosensitive polyimide resin liquid, its preparation method and uses, which is suitable for multilayer metal interconnect wiring in wafer-level packaging and panel-level packaging. Background Technology
[0002] In recent years, with the rapid development of high-density integrated circuit wafer-level packaging (WLP) and panel-level packaging (PLP) technologies, higher requirements have been placed on the comprehensive performance of photosensitive polyimide resins (PSPI), including better photolithography processability, lower curing temperature, higher heat resistance, mechanical properties, and chemical corrosion resistance. Furthermore, as the number of multilayer metal interconnect circuits (RDLs) increases, the thickness of the cured dielectric film also increases. The volume shrinkage accompanying high-temperature curing leads to increased internal stress, often causing overall RDL warping, deformation, or interlayer cracking. Therefore, improving the adhesion between the dielectric resin and the copper wiring and reducing curing internal stress have become crucial challenges that advanced packaging technologies must address.
[0003] In the prior art, US Patent (US 10,546,821 B2) discloses a method for preventing cracking and delamination in multilayer interconnect via structures of integrated circuits. US Patent (US 9,181,381 B2) discloses a photosensitive resin composition with excellent photolithography patterning processability, the cured resin film of which has a low coefficient of thermal expansion, comprising a photopolymerization initiator and a polyimide precursor resin. Chinese Patent (CN 108604062 B) discloses a negative photosensitive resin composition capable of obtaining a cured film with high sensitivity, low taper pattern shape, and excellent heat resistance.
[0004] To address the problems of poor adhesion, high curing temperature, and high internal stress in negative PSPI resin, this invention introduces organosiloxane segments into the main chain structure of photocrosslinkable polyamide ester, and coordinates with components such as photocrosslinking agents, photosensitizers, thermal crosslinking agents, low-temperature curing accelerators, adhesion promoters, and toughening agents to prepare a negative PSPI resin adhesive with high adhesion, low internal stress, and excellent photolithography processability, suitable for multilayer metal interconnect wiring in wafer-level packaging and panel-level packaging. Summary of the Invention
[0005] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:
[0006] This invention first discloses a highly adhesive negative photosensitive polyimide resin adhesive, which is composed of the following components:
[0007] (A) 100 parts by weight of photocrosslinkable polyaminate resin;
[0008] (B) Solvent 50-150 parts by weight;
[0009] (C) 0.01~20 parts by weight of photocurable crosslinking agent;
[0010] (D) 0.01~10 parts by weight of photocuring initiator;
[0011] (E) 0.01~10 parts by weight of photosensitizer;
[0012] (F) 0.01~10 parts by weight of thermal crosslinking agent;
[0013] (G) 0.01~10 parts by weight of low-temperature curing accelerator;
[0014] (H) Polymerization inhibitor 0.01~10 parts by weight;
[0015] (I) Copper discoloration inhibitor 0.01~10 parts by weight;
[0016] (J) 0.01~10 parts by weight of tackifier;
[0017] (K) Toughening agent 0.01~10 parts by weight;
[0018] The photocrosslinkable polyamic acid ester resin (structural formula shown in Formula I) is formed by dissolving hydroxyl-containing acrylates and / or methacrylates with aromatic dianhydrides in an organic solvent, undergoing an esterification reaction under heating to form the corresponding aromatic diacid diester, and then forming the GPC through a polycondensation reaction with an aromatic diamine in the presence of a reactive end-capping agent. The weight-average molecular weight of GPC is 1.0 × 10⁻⁶. 4 ~3.0×10 4 .
[0019] (Formula I)
[0020] Wherein, the structural formula for X1 is as follows:
[0021] ;
[0022] The structure of X2 is as follows:
[0023]
[0024] Y1 = Aromatic diamine;
[0025] R1 = C1-C6 fatty alcohol.
[0026] Further, the aromatic tetracarboxylic dianhydride comprises: aromatic tetracarboxylic dianhydride-1 and aromatic tetracarboxylic dianhydride-2, in a weight ratio of 1 to 100:100; the aromatic tetracarboxylic dianhydride-1 comprises dianhydrides containing siloxane structures, such as 3,3',4,4'-dimethyldiphenylsilane tetracarboxylic dianhydride (44SiDA), 4,4'-tetramethyldisiloxane phthalic anhydride (44PADS), etc.; the aromatic tetracarboxylic dianhydride-2 comprises pyromellitic dianhydride (PMDA), 3,3',4,4'-benzophenone tetracarboxylic dianhydride (44BTDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (44BPDA), 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride (44ODDA), 2,2-bis(3,4-phthalic anhydride)-1,1,1,3,3,3-hexafluoropropane (6FDA), etc.
[0027] Further, the hydroxyl (meth)acrylate includes 2-methacryloyloxyethanol, 2-hydroxy-3-methoxypropyl methacrylate, etc.; the aromatic diamine includes 4,4'-diaminodiphenyl ether (44ODA), 3,4'-diaminodiphenyl ether (34ODA), 1,4-bis(4-aminophenoxy)benzene (144APB), 2,2-bis[4-(4-aminophenoxy)phenyl]propane (BAPP), 1,4-bis(4-amino-2-trifluoromethylphenoxy)benzene (6FAPB), 1,4-bis(4-amino-2-trifluoromethylphenoxy)biphenyl (6FBAB), p-phenylenediamine, m-phenylenediamine, 4,4'-diaminodiphenylmethane (44MDA), and siloxane-containing diamines, etc.; the reactive end-capping agent includes phthalic anhydride, methylphthalic anhydride, phenylethynyl phthalic anhydride, acetic anhydride, aniline, methylamine, etc.
[0028] Furthermore, the solvent includes N-methyl-2-pyrrolidone (NMP), N,N-dimethylacetamide (DMAc), N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), γ-butyrolactone (GBL), acetone, cyclohexanone, ethyl acetate, tetrahydrofuran, ethyl lactate, etc.
[0029] Further, the photocurable crosslinking agent includes diethylene glycol dimethacrylate (2EM), tetraethylene glycol dimethacrylate (4EM), propylene glycol dimethacrylate, polypropylene glycol dimethacrylate, cyclohexane dimethacrylate, 1,4-butanediol dimethacrylate, etc. The photocurable initiator includes benzophenone, 2-hydroxy-2-methylphenylacetone, 1-hydroxycyclohexylphenyl ketone, thioxanthone, 2-methylthioxanthone, benzoyl dimethyl ketal, benzoyl peroxide, etc. The photosensitizer includes 4-morpholinobenzophenone, 4,4'-bis(diethylamino)benzophenone, N-phenyldiethanolamine, 3-acetyl-7-dimethylaminocoumarin, 2-mercaptobenzimidazole, etc.
[0030] Furthermore, the photocuring initiator is selected from benzophenone, 2-hydroxy-2-methylphenylacetone, 1-hydroxycyclohexylphenyl ketone, thioxanthone, 2-methylthioxanthone, benzoyl dimethyl ketal, benzoyl peroxide, 1-phenyl-1,2-propanedione-2-(O-ethoxycarbonyl) oxime, and mixtures thereof in any proportion;
[0031] The photosensitizer is selected from 4-morpholinobenzophenone, 4,4'-bis(diethylamino)benzophenone, N-phenyldiethanolamine, 3-acetyl-7-dimethylaminocoumarin, 2-mercaptobenzimidazole, and mixtures thereof in any proportion.
[0032] Further, the thermal crosslinking agent includes 2,6-dimethoxymethyl-4-tert-butylphenol, 2,6-dimethoxymethyl-p-cresol, 2,6-diacetoxymethyl-p-cresol, etc. The low-temperature curing accelerator includes titanium compounds such as bis(triethanolamine)diisopropoxide titanium, diisopropanol bis(2,4-pentanedione)titanium, tetra(n-butanol)titanium, and tetra(isopropanol)titanium. The polymerization inhibitor includes hydroquinone, N-nitrosodiphenylamine, p-tert-butylcatechol, phenothiazine, ethylenediaminetetraacetic acid, 2,6-di-tert-butyl-p-cresol, etc. The copper discoloration inhibitor includes toluenetriazole, 5-methyl-1H-benzotriazole, 2,6-di-tert-butyl-4-methylphenol, 4,4'-methylenebis(2,6-di-tert-butylphenol), etc. The adhesion promoters include silane coupling agents such as γ-aminopropyltrimethoxysilane, γ-glycidyl etheroxypropyltrimethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, 3-ureidopropyltrimethoxysilane, 3-isocyanate-based trimethoxysilane, and vinyltrimethoxysilane. The toughening agents include thermoplastic polyimide resins, silicone-modified polyimide resins, polymethacrylate resins, polyacrylate resins, thermoplastic polyetherimide resins, and thermoplastic polyetheretherketone resins, etc., with a weight average molecular weight of less than 100,000.
[0033] The present invention also provides a method for preparing any of the above-described resin solutions, comprising the following steps:
[0034] The photocrosslinked polyaminate resin was mixed with a solvent and stirred until dissolved under yellow light and nitrogen protection. The aforementioned functional components were then added and stirred until completely dissolved. The solid content and viscosity were adjusted, and the mixture was filtered to obtain a negative PSPI resin solution. When the solid content of the prepared solution was 10-45 wt.%, the viscosity at room temperature was 100-5500 mPa·s, and the viscosity change rate after standing at room temperature for 7 days was less than 10%.
[0035] The present invention also provides an application of any of the above-mentioned adhesives in wafer-level packaging and panel-level packaging multilayer metal interconnect wiring, including spin coating or inkjet printing to form a film, pre-baking, exposure, development, rinsing, heat curing (180-230°C) to form a three-dimensional pattern, and then forming conductor copper lines by electroplating copper and etching, and repeating the process to form a multilayer RDL structure.
[0036] The beneficial effects of this invention are as follows:
[0037] By introducing siloxane-containing dianhydrides into the polyamic acid ester backbone, and coordinating with photocrosslinkers, thermal crosslinkers, low-temperature curing accelerators, adhesion promoters, and toughening agents, the cured resin film possesses high copper surface adhesion, excellent photolithography processability (resolution ≤8.0 μm, steepness ≥0.5), high mechanical properties (tensile strength ≥100 MPa, elongation at break ≥40%), resistance to damp heat, and resistance to chemical corrosion, with residual internal stress ≤30 MPa. This significantly reduces warpage deformation of the reconstructed wafer and avoids interlayer cracking in the RDL. Detailed Implementation
[0038] Unless otherwise specified, the experimental methods used in the following examples are conventional methods. Unless otherwise specified, the materials and reagents used in the following examples are commercially available.
[0039] 1. Comprehensive performance evaluation method
[0040] The photolithography processability is evaluated by observing the stereolithographic pattern under an optical microscope: if the resolution of the raised strip pattern of the cured resin film stereolithography is ≤8.0µm, the patterns are cleanly developed without foreign matter residue, and the ratio of the bottom width to the top width of the aperture pattern (steepness) is ≥0.5, it is rated as "Excellent"; if the resolution of the raised strip pattern of the cured resin film stereolithography is ≤10.0µm, the patterns are cleanly developed without foreign matter residue, and the ratio of the bottom width to the top width of the aperture pattern (steepness) is ≥0.5, it is rated as "Good"; if the resolution of the raised strip pattern of the cured resin film stereolithography is ≥12.0µm, the patterns are not cleanly developed with foreign matter residue, and the ratio of the bottom width to the top width of the aperture pattern (steepness) is ≥0.5, it is rated as "Poor".
[0041] Photolithography process: Spin-coat the resin onto the surface of a 12-inch silicon wafer, bake at 100-110°C for 1-3 min, place a mask, and expose under UV lamps (i and g lines); develop using cyclopentanone developer, rinse with propylene glycol methyl ether acetate, and cure under nitrogen protection (150°C / 1h, 200°C / 1h, 230°C / 1h) to obtain an 8.0 μm thick cured resin 3D pattern. Resolution ≤ 8.0 μm, steepness ≥ 0.5, and clean development are rated "Excellent"; resolution ≤ 10.0 μm and steepness ≥ 0.5 are rated "Good"; resolution ≥ 12.0 μm or incomplete development are rated "Poor".
[0042] Comprehensive mechanical properties: The adhesive was spin-coated onto the surface of a 12-inch silicon wafer, baked at 120°C for 3 min, exposed to UV light, developed with cyclopentanone, rinsed, and then cured by heating (150°C / 1h, 200°C / 1h, 230°C / 1h). The silicon wafer was then immersed in 47% HF for 5-10 min, rinsed, and an 8.0 μm thick polyimide film was obtained. The film was cut into strips 1.0 cm wide and 9.0 cm long, and tested using a tensile testing machine (speed 50 mm / min). Tensile strength ≥100 MPa and elongation at break ≥40% were rated "Excellent"; tensile strength ≥100 MPa and elongation at break 20%~40% were rated "Good"; elongation at break <20% was rated "Poor".
[0043] Adhesion to copper surface: Cross-cut test (100 grids). 0 grids peeling is "Excellent"; 1-10 grids is "Good"; more than 11 grids is "Poor".
[0044] Moisture and heat resistance: The substrate with the cured film was placed in a 120°C / 2 atm pressure cooker for 200 h, and then subjected to three thermal cycles from room temperature to 260°C. The longitudinal section of the copper-tin protrusion was cut by FIB, and the interface was observed under an optical microscope. No cracks or defects are "excellent"; a few cracks or defects are "good"; and many cracks or defects are "poor".
[0045] Chemical resistance: The cured resin pattern was immersed in a caustic solution (1 wt.% KOH + 39 wt.% 3-methoxy-3-methyl-1-butanol + 60 wt.% DMSO) at 100°C for 1 h. Thickness variation within ±1% and no cracks were rated "Excellent"; ±1.1-3.0% was rated "Good"; and variations exceeding ±3.1-5.0% or the presence of cracks were rated "Poor".
[0046] Residual internal stress: Tested at room temperature using a thin film internal stress tester (FLX-2320). ≤30 MPa is “Excellent”; 31-34 MPa is “Good”; ≥35 MPa is “Poor”.
[0047] Overall performance evaluation: If all indicators are "excellent", the overall score is "excellent"; if one indicator is "good", the overall score is "good"; if one indicator is "poor", the overall score is "poor".
[0048] 2. Example of polyamic acid ester (PAE) resin synthesis
[0049] Resin Synthesis Example 1 (PAE-1-1):
[0050] In a 500 mL three-necked round-bottom flask equipped with a mechanical stirrer, thermometer, and nitrogen protection device, 35.62 g (0.10 mol) of 3,3',4,4'-dimethyldiphenylsilanetetracarboxylic dianhydride (44SiDA), 26.03 g (0.20 mol) of 2-hydroxyethyl methacrylate (HEMA), 15.82 g (0.20 mol) of pyridine, and 129 g of N-methylpyrrolidone (NMP) were added. The mixture was stirred at room temperature for 6 h to produce an aromatic diacid dimethacrylate. The product was then reacted with 23.79 g of SOCl2 at 0-10°C for 2 h, followed by a reaction at room temperature for 4 h to produce a solution of 44SiDA diacyl chloride dimethacrylate.
[0051] In a 1 L three-necked round-bottom flask equipped with a mechanical stirrer, thermometer, and nitrogen protection device, 20.02 g (0.1 mol) of 4,4'-diaminodiphenyl ether (44ODA) and 158 g of NMP were added and stirred to dissolve, forming a homogeneous transparent solution. The above diacyl chloride dimethacrylate solution was added dropwise over 0.5 h, and the reaction was allowed to proceed at room temperature for 10 h. Then, 1.48 g (0.01 mol) of phthalic anhydride was added, and stirring was continued for 1 h. The reaction solution was poured into 5 L of deionized water to precipitate a solid, which was then filtered and vacuum dried to obtain a primary polyaminate resin. This resin was dissolved in tetrahydrofuran, and residual ions were removed by adsorption with anionic and cationic resins to obtain a high-purity polyaminate resin solid (PAE-1-1: 44SiDA-44ODA).
[0052] Resin Synthesis Example 2 (PAE-1-7):
[0053] Following the method of Resin Synthesis Example 1, 35.62 g (0.10 mol) 44SiDA was replaced with a mixture of 17.81 g (0.05 mol) 4,4'-tetramethyldisiloxane phthalic anhydride (44PADS) and 15.53 g (0.05 mol) 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride (ODPA), under the same conditions, to obtain high-purity polyamic acid ester resin solid (PAE-1-7:44PADS / ODPA(1:1)-44ODA).
[0054] Resin Synthesis Example 3 (PAE-1-13):
[0055] Following the method of Resin Synthesis Example 1, 20.02 g (0.1 mol) of 44ODA was replaced with 29.22 g (0.1 mol) of 1,4-bis(3-aminophenoxy)benzene (134APB), and other conditions were the same, to obtain high-purity polyamic acid ester resin solid (PAE-1-13:44PADS / ODPA(1:1)-134APB).
[0056] Resin Synthesis Example 4 (PAE-1-15):
[0057] Following the method of Resin Synthesis Example 1, 20.02 g (0.1 mol) of 44ODA was replaced with 41.03 g (0.1 mol) of 2,2-bis[4-(4-aminophenoxy)phenyl]propane (BAPP), and all other conditions were the same, to obtain high-purity polyamic acid ester resin solid (PAE-1-15:44PADS / ODPA(1:1)-BAPP).
[0058] Resin Synthesis Example 5 (PAE-1-16):
[0059] Following the method of Resin Synthesis Example 1, 20.02 g (0.1 mol) of 44ODA was replaced with 42.82 g (0.1 mol) of 1,4-bis(4-amino-2-trifluoromethylphenoxy)benzene (6FAPB), and other conditions were the same, to obtain high-purity polyamic acid ester resin solid (PAE-1-16:44PADS / ODPA(1:1)-6FAPB).
[0060] Comparative Synthesis Example 1 (PAE-2-1):
[0061] Following the method of Resin Synthesis Example 1, 35.62 g (0.10 mol) 44SiDA was replaced with 44.42 g (0.10 mol) 2,2-bis(4-benzenetetrahydric anhydride)hexafluoropropane (6FDA), and all other conditions were the same, to obtain high-purity polyamic acid ester resin solid (PAE-2-1:6FDA-44ODA).
[0062] Comparative Synthesis Example 2 (PAE-2-3):
[0063] Following the method of resin synthesis example 2, 17.81 g (0.05 mol) 44PADS was replaced with 15.53 g (0.05 mol) 2,3',3,4'-diphenyl ether tetracarboxylic dianhydride (34ODPA), and other conditions were the same, to obtain high-purity polyamic acid ester resin solid (PAE-2-3:34ODPA / BPDA(1:1)-44ODA).
[0064] 3. Examples and Comparative Examples of Negative Photosensitive PSPI Resin Liquid
[0065] Example 1:
[0066] In a cleanroom equipped with a yellow light, 100 g of PAE-1-1 prepared in Resin Synthesis Example 1 was weighed and dissolved in a mixed solvent of 80 g NMP and 20 g ethyl lactate (EL) to form a homogeneous solution. Then, 8 g tetraethylene glycol dimethacrylate (4EM), 1.0 g 1-phenyl-1,2-propanedione-2-(O-ethoxycarbonyl)oxime, 2.5 g 2,6-dimethoxymethyl-4-tert-butylphenol, 0.5 g bis(triethanolamine)diisopropoxide titanium, 0.5 g 5-methyl-1H-benzotriazole, 0.5 g N-phenyldiethanolamine, 0.5 g γ-glycidyl etheroxypropyltrimethoxysilane, and 0.5 g N-nitrosodiphenylamine were added sequentially. The mixture was stirred at room temperature for 1 h to obtain a negative PSPI resin solution. The solids content was 35 wt.%, and the viscosity was 3500 mPa·s.
[0067] The above-mentioned adhesive solution was spin-coated onto the surface of a 12-inch silicon wafer, baked at 100-110°C for 1-3 min, a mask was placed, and exposed to ultraviolet light (i and g lines); cyclopentanone developer was spray-developed, propylene glycol methyl ether acetate was rinsed, and the film was cured under nitrogen protection by heating (150°C / 1h, 200°C / 1h, 230°C / 1h) to obtain a stereolithographic pattern of the cured polyimide film.
[0068] Performance evaluation: ① Copper adhesion 0 / 100, excellent; ② Photolithography processability: steepness 0.50, resolution 7.9 μm, excellent; ③ Mechanical properties: tensile strength 100 MPa, elongation at break 45%, excellent; ④ Resistance to damp heat: no microcracks or defects, excellent; ⑤ Resistance to chemical etching: film thickness change rate 0.85%, excellent; ⑥ Residual internal stress 29 MPa, excellent; ⑦ Overall evaluation: excellent.
[0069] Example 2:
[0070] In Example 1, PAE-1-1 was replaced with PAE-1-7, while all other aspects remained the same, resulting in a negative PSPI resin solution. Performance evaluation: ① Copper adhesion 0 / 100, excellent; ② Photolithography processability: steepness 0.65, resolution 7.5 μm, excellent; ③ Mechanical properties: tensile strength 110 MPa, elongation at break 47%, excellent; ④ Resistance to damp heat: excellent; ⑤ Resistance to chemical corrosion: film thickness change rate 0.76%, excellent; ⑥ Residual internal stress 28 MPa, excellent; ⑦ Overall evaluation: excellent.
[0071] Example 3:
[0072] In Example 1, PAE-1-1 was replaced with PAE-1-13, while all other aspects remained the same, resulting in a negative PSPI resin solution. Performance evaluation: ① Copper adhesion 0 / 100, excellent; ② Photolithography processability: steepness 0.65, resolution 7.5 μm, excellent; ③ Mechanical properties: tensile strength 110 MPa, elongation at break 47%, excellent; ④ Resistance to damp heat: excellent; ⑤ Resistance to chemical corrosion: film thickness change rate 0.76%, excellent; ⑥ Residual internal stress 28 MPa, excellent; ⑦ Overall evaluation: excellent.
[0073] Example 4:
[0074] In Example 1, PAE-1-1 was replaced with PAE-1-15, while all other aspects remained the same, resulting in a negative PSPI resin solution. Performance evaluation: ① Copper adhesion 0 / 100, excellent; ② Photolithography processability: steepness 0.66, resolution 7.8 μm, excellent; ③ Mechanical properties: tensile strength 110 MPa, elongation at break 43%, excellent; ④ Resistance to damp heat: excellent; ⑤ Resistance to chemical corrosion: film thickness change rate 0.73%, excellent; ⑥ Residual internal stress 27 MPa, excellent; ⑦ Overall evaluation: excellent.
[0075] Example 5:
[0076] In Example 1, PAE-1-1 was replaced with PAE-1-16, while all other aspects remained the same, resulting in a negative PSPI resin solution. Performance evaluation: ① Copper adhesion 0 / 100, excellent; ② Photolithography processability: steepness 0.73, resolution 7.6 μm, excellent; ③ Mechanical properties: tensile strength 120 MPa, elongation at break 48%, excellent; ④ Resistance to damp heat: excellent; ⑤ Resistance to chemical corrosion: film thickness change rate 0.78%, excellent; ⑥ Residual internal stress 27 MPa, excellent; ⑦ Overall evaluation: excellent.
[0077] Comparative Example 1:
[0078] PAE-1-1 in Example 1 was replaced with PAE-2-1 in Comparative Synthesis Example 1, with all other aspects remaining the same, to obtain a negative PSPI resin solution. Performance evaluation: ① Copper adhesion 8 / 100, good; ② Photolithography processability: steepness 0.66, resolution 9.6μm, good; ③ Mechanical properties: tensile strength 125 MPa, elongation at break 48%, excellent; ④ Resistance to damp heat: excellent; ⑤ Resistance to chemical corrosion: film thickness change rate 0.74%, excellent; ⑥ Residual internal stress 32 MPa, good; ⑦ Overall evaluation: good.
[0079] Comparative Example 2:
[0080] PAE-1-1 in Example 1 was replaced by PAE-2-3 in Comparative Synthesis Example 2, with all other aspects remaining the same, to obtain a negative PSPI resin solution. Performance evaluation: ① Copper adhesion 12 / 100, poor; ② Photolithography processability: steepness 0.63, resolution 7.6μm, excellent; ③ Mechanical properties: tensile strength 130 MPa, elongation at break 48%, excellent; ④ Resistance to damp heat: excellent; ⑤ Resistance to chemical etching: film thickness change rate 0.78%, excellent; ⑥ Residual internal stress 37 MPa, poor; ⑦ Overall evaluation: poor.
[0081] Table 1 Performance comparison of Examples 1-5 and Comparative Examples 1-2
[0082] project Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 PAE-1 44SiDA-44ODA 44PADS / ODPA-44ODA 44PADS / ODPA-134APB 44PADS / ODPA-BAPP 44PADS / ODPA-6FAPB 6FDA-44ODA 34ODPA / BPDA-44ODA Solid content (wt.%) 35±2.0 35±2.0 35±2.0 35±2.0 35±2.0 35±2.0 35±2.0 Viscosity (mPa·s, 23℃) 3500±100 3500±100 3500±100 3500±100 3500±100 3500±100 3500±100 Curing temperature (°C) 220 / 1h 220 / 1h 220 / 1h 220 / 1h 220 / 1h 220 / 1h 220 / 1h ① Copper adhesion / 100-cross test 0 / 100 Excellent 0 / 100 Excellent 0 / 100 Excellent 0 / 100 Excellent 0 / 100 Excellent 8 / 100 good 12 / 100 Poor ② Photolithography processability (steepness / resolution) 0.50 / 7.9μm Excellent 0.65 / 7.5μm Excellent 0.65 / 7.5μm Excellent 0.66 / 7.8μm Excellent 0.73 / 7.6μm Excellent 0.66 / 9.6μm fine 0.63 / 7.6μm Excellent ③ Mechanical properties (tensile strength / elongation) 100MPa / 45% Excellent 110MPa / 47% excellent 110MPa / 47% excellent 110MPa / 43% Excellent 120MPa / 48% excellent 125MPa / 48% Excellent 130MPa / 48% excellent ④ Resistance to damp heat excellent excellent excellent excellent excellent excellent excellent ⑤ Chemical resistance (film thickness change rate) 0.85% Excellent 0.76% Excellent 0.76% Excellent 0.73% Excellent 0.78% Excellent 0.74% Excellent 0.78% Excellent ⑥ Residual internal stress 29MPa Excellent 28MPa Excellent 28MPa Excellent 27MPa Excellent 27MPa Excellent 32MPa good 37MPa difference ⑦ Overall Evaluation excellent excellent excellent excellent excellent good Difference
[0083] The results show that PAE resin prepared by compounding aromatic tetracarboxylic dianhydrides (such as 44SiDA and 44PADS) with conventional dianhydrides, and the resulting negative PSPI resin solution with components such as photocrosslinkers, photosensitizers, thermal crosslinkers, adhesion promoters, and toughening agents, significantly improves copper surface adhesion and reduces residual internal stress while maintaining excellent photolithography processability, resistance to damp heat, and chemical etching resistance. When conventional dianhydrides (such as 6FDA and 34ODPA) without siloxane structures are used, the copper surface adhesion and / or residual internal stress indicators deteriorate significantly, and the overall evaluation drops to "good" or "poor".
[0084] The specific embodiments described above do not constitute a limitation on the scope of protection of this application. Those skilled in the art should understand that various modifications, combinations, sub-combinations, and substitutions can be made according to design requirements and other factors. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of this application should be included within the scope of protection of this application.
Claims
1. A highly adhesive negative photosensitive polyimide resin adhesive, comprising the following components: (A) 100 parts by weight of photocrosslinkable polyaminate resin; (B) Solvent 50-150 parts by weight; (C) 0.01~20 parts by weight of photocurable crosslinking agent; (D) 0.01~10 parts by weight of photocuring initiator; (E) 0.01~10 parts by weight of photosensitizer; (F) 0.01~10 parts by weight of thermal crosslinking agent; (G) 0.01~10 parts by weight of low-temperature curing accelerator; (H) Polymerization inhibitor 0.01~10 parts by weight; (I) Copper discoloration inhibitor 0.01~10 parts by weight; (J) 0.01~10 parts by weight of tackifier; (K) Toughening agent 0.01~10 parts by weight; The photocrosslinkable polyamic acid ester resin contains methacrylate groups in its main chain structure that can undergo photocrosslinking reaction after being irradiated with ultraviolet light.
2. The resin adhesive according to claim 1, wherein: The photocrosslinkable polyamic acid ester resin is formed by esterification and acyl chloride reactions of hydroxyl-containing acrylates and / or methacrylates with aromatic tetracarboxylic dianhydrides to form corresponding aromatic diacid diesters, which are then polycondensed with aromatic diamines in the presence of a reactive end-capping agent. The GPC has a weight-average molecular weight of 1.0 × 10⁻⁶. 4 ~3.0×10 4 ; The photocrosslinked polyamic acid ester resin has the structural formula shown in Formula I: (Equation I) The structure of X1 is as follows: ; The structure of X2 is as follows: ; Y1 = Aromatic diamine; R1 = C1-C6 fatty alcohol.
3. The resin adhesive according to claim 2, wherein: The aromatic tetracarboxylic dianhydride includes: aromatic tetracarboxylic dianhydride-1 and aromatic tetracarboxylic dianhydride-2, wherein the weight ratio of aromatic tetracarboxylic dianhydride-1 to aromatic tetracarboxylic dianhydride-2 is 1~100:100; The aromatic tetracarboxylic dianhydride-1 is selected from 3,3',4,4'-dimethyldiphenylsilane tetracarboxylic dianhydride, 2,3',2,3'-dimethyldiphenylsilane tetracarboxylic dianhydride, 4,4'-tetramethyldisiloxane phthalic anhydride, 3,3',4,4'-methyltriphenylsilane tetracarboxylic dianhydride, 3,3',4,4'-tetraphenylsilane tetracarboxylic dianhydride, 4,4'-bis(dimethylsilylphenyl)diphthalic anhydride, and mixtures thereof in any proportion; The aromatic tetracarboxylic dianhydride-2 is selected from pyromellitic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride, 3,3',4,4'-diphenyl sulfone tetracarboxylic dianhydride, 2,2-bis(3,4-phthalic anhydride)-1,1,1,3,3,3-hexafluoropropane and mixtures thereof in any proportion.
4. The resin adhesive according to claim 2, wherein: The aromatic diamine is selected from 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 1,4-bis(4-aminophenoxy)benzene, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 1,4-bis(4-amino-2-trifluoromethylphenoxy)benzene, p-phenylenediamine, m-phenylenediamine, 4,4'-diaminodiphenylmethane, 1,3-bis(3-aminopropyl)tetramethyldisiloxane, 1,3-bis(3-aminophenoxy)tetramethyldisiloxane, and mixtures thereof in any proportion.
5. The resin adhesive according to claim 2, wherein: The reactive end-capping agent is selected from phthalic anhydride, 3-methylphthalic anhydride, 4-methylphthalic anhydride, 4-phenylethynylphthalic anhydride, acetic anhydride, aniline, 3-methylaniline, 4-methylaniline, methylamine, ethylamine, and mixtures thereof in any proportion.
6. The resin adhesive according to claim 1, wherein: The solvent is selected from N-methyl-2-pyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide, γ-butyrolactone, acetone, cyclohexanone, ethyl acetate, tetrahydrofuran, ethyl lactate, and mixtures thereof in any proportion.
7. The resin adhesive according to claim 1, wherein: The photocurable crosslinking agent is selected from diethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, propylene glycol dimethacrylate, polypropylene glycol dimethacrylate, cyclohexane dimethacrylate, 1,4-butanediol dimethacrylate, and mixtures thereof in any proportion. The photocuring initiator is selected from benzophenone, 2-hydroxy-2-methylphenylacetone, 1-hydroxycyclohexylphenyl ketone, thioxanone, 2-methylthioxanone, benzoyladium dimethyl ketal, benzoyl peroxide, 1-phenyl-1,2-propanedione-2-(O-ethoxycarbonyl) oxime and mixtures thereof in any proportion; The photosensitizer is selected from 4-morpholinobenzophenone, 4,4'-bis(diethylamino)benzophenone, N-phenyldiethanolamine, 3-acetyl-7-dimethylaminocoumarin, 2-mercaptobenzimidazole, and mixtures thereof in any proportion.
8. The resin adhesive according to claim 1, wherein: The thermal crosslinking agent is selected from 2,6-dimethoxymethyl-4-tert-butylphenol, 2,6-dimethoxymethyl-p-cresol, 2,6-diacetoxymethyl-p-cresol, and mixtures thereof in any proportion; The low-temperature curing accelerator is selected from bis(triethanolamine) diisopropoxide titanium, diisopropoxide bis(2,4-pentanedione) titanium, tetra(n-butanol) titanium, tetra(isopropanol) titanium, and mixtures thereof in any proportion; The polymerization inhibitor is selected from hydroquinone, N-nitrosodiphenylamine, p-tert-butylcatechol, phenothiazine, ethylenediaminetetraacetic acid, 2,6-di-tert-butyl-p-cresol, and mixtures thereof in any proportion; The copper color-changing inhibitor is selected from toluenetriazole, 5-methyl-1H-benzotriazole, 2,6-di-tert-butyl-4-methylphenol, 4,4'-methylenebis(2,6-di-tert-butylphenol), and mixtures thereof in any proportion. The adhesive is selected from γ-aminopropyltrimethoxysilane, γ-glycidyl ether oxypropyltrimethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, 3-ureidopropyltrimethoxysilane, 3-isocyanate-based trimethoxysilane, vinyltrimethoxysilane, and mixtures thereof in any proportion; The toughening agent is selected from thermoplastic polyimide resin, silicone-modified polyimide resin, polymethyl methacrylate resin, polyacrylate resin, thermoplastic polyetherimide resin, thermoplastic polyetheretherketone resin, and mixtures thereof in any proportion.
9. A method for preparing a resin adhesive according to any one of claims 1 to 8, comprising the following steps: (1) The photocrosslinked polyamic acid ester resin is mixed with a solvent and stirred and dissolved under yellow light and nitrogen protection to form a homogeneous solution; (2) Add photocurable crosslinking agent, photocurable initiator, photosensitive accelerator, thermal crosslinking agent, low temperature curing accelerator, polymerization inhibitor, copper discoloration inhibitor, adhesion promoter and toughening agent, and stir until completely dissolved to form a homogeneous solution under yellow light zone and nitrogen protection; (3) Add an appropriate amount of solvent to adjust the solid content and viscosity of the solution, and finally filter to obtain negative PSPI resin solution; in, The preparation method of the photocrosslinkable polyamic acid ester resin includes: 1) Hydroxyl-containing acrylates and / or methacrylates and aromatic dianhydrides are dissolved in an organic solvent and subjected to esterification under heating to form aromatic diester diacids; 2) The aromatic diester diacid is reacted with thionyl chloride to form aromatic diester diacyl chloride; 3) Under cooling conditions, the aromatic diamine solid is added in portions to the above aromatic diester diacyl chloride solution and stirred to react; then a reactive end-capping agent is added and the reaction is continued to be stirred to form a photocrosslinked polyamic acid ester resin solution; the resin solution is dispersed in a poor solvent, the solid is precipitated, filtered, washed and dried, and then dissolved in a solvent. The residual ions are removed by adsorption with anionic and / or cationic resins to obtain high-purity photocrosslinked polyamic acid ester resin.
10. The application of a resin adhesive according to any one of claims 1 to 8 in multilayer metal interconnect wiring for wafer-level packaging and panel-level packaging.
Citation Information
Patent Citations
Negative photosensitive resin composition, cured film, display device having cured film, and method of manufacturing thereof.
CN108604062B
Opening in a multilayer polymeric dielectric layer without delamination
US10546821B2
Photosensitive resin composition and cured film
US9181381B2